Edukasi Pembuatan Obat Luka Berbasis Bahan Alam - Sutrisno, Deny; Perawati, Santi; Mariska, Ruri Putri; Andriani, Lili; Aliyah, Siti Hamidatul (Universitas Baiturrahim, 2024)
One of the schools that consistently participates around STIKES Harapan Ibu Jambi is SD Negeri 43/IV Kota Jambi, which is located quite close to the educational institution. In order to enhance the knowledge of the students, specific programs need to be implemented to educate the students of SD Negeri 43/IV Kota Jambi in the field of health, particularly in wound management using natural resources. The methods used in this community service activity include lectures, discussions, and demonstrations to the students of SD Negeri 43/IV Kota Jambi. Education on the production of natural-based wound treatments, especially using the leaves of Mikania micrantha Kunth. and other natural materials, has been successfully conveyed to the students in SD Negeri 43/IV Kota Jambi. As a result, the students have gained a better understanding of producing natural wound remedies from the surrounding natural resources and have also been able to formulate these remedies.